Azadirachta Indica Extract (Neem) as skin solution soap / Mazni Musa... [et al.] - Musa, Mazni; Abdul Rahman, Norul Azilah; Said, Nur Rahimah; Abdul Halim, Nurul Huda; Mohamed Sapari, Jamil (Universiti Teknologi MARA, Negeri Sembilan, 2019)
A local herb known as neem (semambu) or its scientific name Azadirachta indica has been used extensively in traditional treatment due to its medicinal properties. Neem leaves have been used traditionally for treating several epidermal dysfunctions, such as eczema, psoriasis, and acne. Neem is rich in antioxidants and helps to boost immune response in tissues of affected skin area. It also consists of bioactive compounds for antibacterial, antifungal, and anticancer activities. In this study, neem leaves extract was used in producing herbal neem soap as a remedy for curing skin problems. The herbal neem soap was made by blending 36.4% palm oil, 9.1% coconut oil, 27.3% sodium hydroxide, 9.1% neem oil extract, and 18.2% neem aqueous extract which formed a pale yellow soap base. The results of the selected physical and chemical properties of this study show that the moisture content of the soap was 4.02% with 10.60 pH value, 57.40% total fatty matter, and 0.44% free caustic alkali. The results imply that herbal neem soap is suitable for human skin and can be a therapeutic alternative to skin problems.